1993
DOI: 10.1017/s0317167100048617
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Dehydrogenase Deficiency in Cerebellar Degenerations: Clinical, Biochemical and Molecular Genetic Aspects

Abstract: Glutamate dehydrogenase (GDH), an enzyme central to glutamate metabolism, is significantly reduced in patients with heterogenous neurological disorders characterized by multiple system atrophy (MSA) and predominant involvement of the cerebellum and its connections. In human brain, GDH exists in multiple isoforms differing in their isoelectric point and molecular mass. These are differentially reduced in quantity and altered in catalytic activity in patients with clinically distinct forms of MSA, thus suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 44 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Castro et al found that PHS reduced the viability of cells and induced apoptosis in Neurospora crassa [ 55 ]. D-Aspartic acid participates in alanine, aspartate and glutamate metabolism, while glutamate dehydrogenase (GDH) is a central enzyme in glutamate metabolism [ 56 ]. The enhancement of drought resistance in wheat is related to ammonia assimilation and increased NADH-GDH activity under low or high osmotic stress [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al found that PHS reduced the viability of cells and induced apoptosis in Neurospora crassa [ 55 ]. D-Aspartic acid participates in alanine, aspartate and glutamate metabolism, while glutamate dehydrogenase (GDH) is a central enzyme in glutamate metabolism [ 56 ]. The enhancement of drought resistance in wheat is related to ammonia assimilation and increased NADH-GDH activity under low or high osmotic stress [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olivopontocerebellar atrophy is a common disease related to ataxia and Parkinson's-like diseases. The neurodegenerative process is linked with GDH (glycerate dehydrogenase) deficiency [ 58 ]. The regulation of diabetes is caused by genes including ASNS, CAD, GMPS, and PHGDH.…”
Section: Discussionmentioning
confidence: 99%